Structures of the intermediates of Kok's photosynthetic water oxidation clock. (15th November 2018) - Kern, Jan; Chatterjee, Ruchira; Young, Iris; Fuller, Franklin; Lassalle, Louise; Ibrahim, Mohamed; Gul, Sheraz; Fransson, Thomas; Brewster, Aaron; Alonso-Mori, Roberto; Hussein, Rana; Zhang, Miao; et al.
Abstract Inspired by the period-four oscillation in flash-induced oxygen evolution of photosystem II discovered by Joliot in 1969, Kok performed additional experiments and proposed a five-state kinetic model for photosynthetic oxygen evolution, known as Kok's S-state clock or cycle1, 2 . The model comprises four (meta)stable intermediates (S0, S1, S2 and S3 ) and one transient S4 state, which precedes dioxygen formation occurring in a concerted reaction from two water-derived oxygens bound at an oxo-bridged tetra manganese calcium (Mn4 CaO5 ) cluster in the oxygen-evolving complex3–7 . This reaction is coupled to the two-step reduction and protonation of the mobile plastoquinone QB at the acceptor side of PSII. Here, using serial femtosecond X-ray crystallography and simultaneous X-ray emission spectroscopy with multi-flash visible laser excitation at room temperature, we visualize all (meta)stable states of Kok's cycle as high-resolution structures (2.04–2.08 Å). In addition, we report structures of two transient states at 150 and 400 µs, revealing notable structural changes including the binding of one additional 'water', Ox, during the S2 →S3 state transition. Our results suggest that one water ligand to calcium (W3) is directly involved in substrate delivery. The binding of the additional oxygen Ox in the S3 state between Ca and Mn1 supports O–O bond formation mechanisms involving O5 as one substrate, where Ox is either the other substrate oxygen or is perfectly positioned to refill the O5 position during O2 release. Thus, our results exclude peroxo-bond formation in the S3 state, and the nucleophilic attack of W3 onto W2 is unlikely. Crystallography and spectroscopy are used to solve high-resolution structures of the intermediates of Kok's S-state clock in photosystem II.